2021
DOI: 10.1016/j.sjbs.2021.05.064
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characteristics and targeted encapsulated Cordia myxa fruits extracts nanoparticles for antioxidant and cytotoxicity potentials

Abstract: A promising Cordia myxa fruit (CMF) extract targets an additional incorporation in functional foods. It retains appropriate health welfares owing to its antioxidant properties with limited incorporation in food matrices due its hydrophobicity. Therefore, CMF extract micro- and nanocapsulation was performed to protect and facilitate consistency of produced hydrophobic foods matrices. Furthermore, to determine its phytochemicals, antioxidant, and cytotoxic effects by applying analytical HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Plates were washed three times with 1% acetic acid and air-dried overnight. Then, 150 μL of 10 mM trisaminomethane (TRIS) was added to dissolve the protein-bound SRB stain; the absorbance was measured at 540 nm using a BMG LABTECH ® -FLUOstar Omega microplate reader (Ortenberg, Germany) [45].…”
Section: Determination Of the Scgs Cytotoxic Effect Using Sulforhodamine B (Srb) Assaymentioning
confidence: 99%
“…Plates were washed three times with 1% acetic acid and air-dried overnight. Then, 150 μL of 10 mM trisaminomethane (TRIS) was added to dissolve the protein-bound SRB stain; the absorbance was measured at 540 nm using a BMG LABTECH ® -FLUOstar Omega microplate reader (Ortenberg, Germany) [45].…”
Section: Determination Of the Scgs Cytotoxic Effect Using Sulforhodamine B (Srb) Assaymentioning
confidence: 99%
“…The antioxidant potential of flour blends and biscuit samples was due to the presence of antioxidants and bioactive compounds in DPF and APF. Furthermore, Habib et al [ 51 ] and El-Massry et al [ 52 ] suggested that epicatechin, catechin, gentisic acid, and chrysin were the phytochemicals present in DPF and APF with a potent antioxidant potential. The mechanism responsible for the antioxidant activity of the samples was linked with the availability of antioxidants present in DPF and APF, which function as reducing agents and neutralize the formation of the free-radical chain reaction by the donation of electrons, which ultimately restricting the synthesis of peroxides [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The extract inhibited cell proliferation less effectively against the HepG2 cell line. Further, micro and nanocapsules showed a very low cytotoxicity [ 33 ]. In our current study, the growth inhibition of various extracts and fractions deviated somewhat from that described in the literature.…”
Section: Discussionmentioning
confidence: 99%